Study into the factors contributing to the continued development of talented and elite youth athletes into elite senior level using a developmental and holistic perspective - Rosier, N.; Wylleman, P.; de Bosscher, V.; van Hoecke, J.; Reints, A.; Tekavc, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Researchers have examined how talented athletes develop through (as well as after) their athletic career. While different normative challenges have been studied (e.g., initiation into competitive sport, dropout from competitive sport, retirement from elite sport), few empirical data is available on the challenges talented athletes face during as well as after making the junior-senior transition. Methods: Taking into account the multi-level factors of influence on career development, the developmental lifespan model (Wylleman & Reints, 2010) was used as conceptual framework to conduct a preliminary study into the empirical data available on the junior-senior transition. Results: At athletic development the junior-senior transition generally entails that first-year senior athletes will generally be at a lower end in terms of athletic prowess and/or achievement and that, on average, only one junior elite athlete in three actually makes a successful transition into senior elite ranks. In comparison to challenges faced at other levels of development (e.g., psychological, academic) this transition is also a `point of no return` as athletes cannot return to an earlier period or point in their athletic career. As the junior-senior transition occurs during adolescence, talented athletes will face challenges at psychological level including developing an own identity, coping with unexpected situations, higher expectations and pressures, and developing higher self-initiated/self-regulated behaviors. At psychosocial level, it was found that at the onset of the junior-senior transition, coaches become more personally involved, emphasize more the technical proficiency, and expect from them progress through discipline and hard work; with first-year senior athletes, coaches were found to make them more responsible for the training and competitions, as well as placing great demands upon them. At academic level, talented athletes will in first instance face challenges as they make the transition out of secondary education; during and after the junior-senior transition those talented athletes who continue into higher education will in second instance be required as `student-athletes` to cope with challenges that strongly differ from that at secondary education level. Discussion: As past research has been restricted (e.g., retrospective, limited number of participants, restricted to characteristics at athletic level), a clear need exists for research allowing not only to understand the developmental (stage-like) process occurring during the junior-to-senior process but also to look beyond the individual athlete characteristics and take into account the (structural and organisational aspects) of the environment in which talents develop.